Dr. Marko Ilešič (1947-2024) - Pavliha, Marko (Pravnik, 2024)
The text was prepared based on the author’s speech at the mourning session in memory of Marko Ilešič, PhD, which was organised on 28 June 2024 at the Faculty of Law at the University of Ljubljana by the Faculty and the Association of Law Societies of Slovenia. It is largely based on the preface to the monograph Challenges of Law in Reality of Life: Liber Amicorum Marko Ilešič (Faculty of Law, Ljubljana 2017), edited by Marko Pavliha, Ada Polajnar-Pavčnik, Boštjan Koritnik, and Darja Ilešič Čokl. The book includes 46 brilliant scientific, professional and essayistic compositions prepared by a broad variety of Ilešič’s friends, former and current colleagues. Marko Ilešič, PhD, born in 1947, was an outstanding lawyer, a remarkable human being, a polyglot, and a passionate sports enthusiast, particularly in football. He made his most significant professional contribution as a judge of the Court of Justice of the European Union, serving from 2004 until his untimely death. This obituary highlights some of Marko Ilešič’s notable career achievements and his esteemed reputation among his peers in the fields of law, sports, and beyond. It also pays special attention to the personality qualities of Marko Ilešič that made him an extremely popular and sought-after interlocutor, colleague, and friend.
Keywords: Ilešič, Marko; nekrologi; življenjepisi